IB - Ganguli, B.N. (New Delhi, 1973)
The present work is meaningful effort, on the part of a renowned economist to deal with the wider interconnections of population growth and development. It is an introductory reader on the subject meant for the student and the citizen. It is illustrative in its treatment of an integrated approach to our basic national problems.
Keywords: Population